Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1111/j.1574-6968.1996.tb08458.x
|View full text |Cite
|
Sign up to set email alerts
|

Peroxidase-catalyzed generation of catechin oligomers that inhibit glucosyltransferase fromStreptococcus sobrinus

Abstract: Oolong tea extract (OTE) and the purified polymeric polyphenols from OTE have been found to inhibit glucosyltransferase (GTase) of mutans streptococci. In view of the partial fermentation characteristic of oolong tea, we describe here an in vitro model reaction system to produce partially fermented products of D-(+)-catechin or green tea extract (GTE) using horseradish peroxidase. A dimeric catechin molecule was identified as dehydro-dicatechin A by instrumental analyses. The molecular size of some oligomeric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(14 citation statements)
references
References 15 publications
0
13
0
1
Order By: Relevance
“…Numerous biological activities have been reported for green tea and its contents, among them, the preventive effects against cancer are most notable. Peroxidase catalyzed the oxidative polymerization of catechin to produce the oligomer with a degree of polymerization less than 5 . Kinetic study on the oxidation of catechin by peroxidase from strawberries showed highly efficient catalytic activity of the enzyme at low concentration of hydrogen peroxide. , The reaction products obtained by the HRP catalyst were analyzed by reversed-phase and size-exclusion chromatographies. , The products obtained by using HRP and polyphenol oxidase as catalysts were comparably studied.…”
Section: Oxidoreductasesmentioning
confidence: 99%
“…Numerous biological activities have been reported for green tea and its contents, among them, the preventive effects against cancer are most notable. Peroxidase catalyzed the oxidative polymerization of catechin to produce the oligomer with a degree of polymerization less than 5 . Kinetic study on the oxidation of catechin by peroxidase from strawberries showed highly efficient catalytic activity of the enzyme at low concentration of hydrogen peroxide. , The reaction products obtained by the HRP catalyst were analyzed by reversed-phase and size-exclusion chromatographies. , The products obtained by using HRP and polyphenol oxidase as catalysts were comparably studied.…”
Section: Oxidoreductasesmentioning
confidence: 99%
“…The pathogenicity is closely related to the production of extracellular, water insoluble glucans from sucrose by glucosyltransferase and acid release from various fermentable sugars. Poly(catechin) obtained using HRP catalyst in a phosphate buffer (pH ¼ 6) markedly inhibited glucosyltransferase from Streptococcus sorbrinus 6715, [48] whereas the inhibitory effect of catechin for this enzyme was very low.…”
Section: Enzymatically Polymerized Flavonoidsmentioning
confidence: 99%
“…Another enzyme utilized in the polymerization of flavonoids is horseradish peroxidase (HRP). As a result of the reaction with horseradish peroxidase, the polymeric structures of catechin [12,13,26] and quercetin [27] were synthesized. The enzymatic reactions of polyphenols influenced their biological activity.…”
Section: Introductionmentioning
confidence: 99%